G335(P) Phenytoin dosing and serum concentrations in paediatric patients requiring 20 mg/kg intravenous loading dose. (7th April 2014) - Piper, J; Hawcutt, D; Verghese, G; Spinty, S; Newland, P; Appleton, R
Abstract : Aim: Phenytoin's loading dose for refractory tonic-clonic seizures in children was changed from 18 mg/kg to 20 mg/kg in January 2011 to reduce the theoretical risk of miscalculation. Phenytoin has complex pharmacokinetics and there is no data on the effectiveness and safety of the new dose. Therefore we aimed to measure the intravenous levels of phenytoin in children to assess the effectiveness, safety and toxicity of this new dosing regimen. Methods: The use of intravenous loading doses of phenytoin was audited over 27 months to evaluate the pharmacokinetic, clinical and toxic effects of the new dose in clinical practice. Current clinical practice at our institution is to measure the total serum phenytoin concentrations 1–3 h post loading dose, aiming for a level 10–20 µg/ml. Serum phenytoin concentrations were compared with both dose (weight adjusted) and time. Results: Serum phenytoin concentrations were measured on 46 occasions from 41 children (38 retrospective and 8 prospective), of which 24 were within 60–180 (median 105) minutes following completion of infusion of the loading dose. Use of estimated weights meant patients received between 15.5 and 27.5 mg/kg (78–138% expected dose). Supra-therapeutic serum concentrations (>20 µg/ml were present in 5/24 (20.1%) (three using actual weight, two using estimated). Three adverse effects consistent with phenytoin toxicity were noted in children with supra-therapeutic concentrations. Two errors in dose prescriptions were found. Conclusion: The new intravenous 20 mg/kg loading dose has similar percentage of therapeutic and supra-therapeutic serum phenytoin concentrations to previously published estimates for the 18 mg/kg dose. However, there are a greater number of potentially associated toxicities than in previous studies at the lower dose. A wide range of doses continue to be applied due to errors in estimated weight, giving up to 138% of the expected dose in this cohort. The new regime is also not immune to prescribing errors. Despite its efficacy, the variable pharmacokinetic and toxicity profiles strengthens the case for finding alternative anti-epileptics in status epilepticus.